Pulmonary fibrotic response to inhalation of ZnO nanoparticles and toluene co-exposure through directed flow nose only exposure chamber. (November 2013) - Jain, Sonam; Rachamalla, Mahesh; Kulkarni, Apoorva; Kaur, Jasmine; Tikoo, Kulbhushan
Abstract The increasing use of Zinc Oxide nanoparticles (ZnONPs) in paint industry is not supplemented with adequate toxicology data. This report focuses on the fibrogenic toxicity caused due to co-exposure of ZnONPs and toluene in male Wistar rats, exposed for 28 days, through directed flow nose only exposure chamber. The rats were grouped as air control, toluene control (200 ppm), zinc oxide control (10 mg/m3), low dose co-exposed (5 mg/m3 ZnO and 200 ppm of toluene) and high dose co-exposed (10 mg/m3 of ZnO and 200 ppm of toluene). Our study demonstrates that co-exposure of ZnONPs and toluene (as in paint industry), even at their respective permissible exposure level (5 mg/m3 for ZnO and 200 ppm for toluene) have the potential to produce a progressive inflammatory and fibrotic response in the alveolar tissues of the lungs. We observed a significant increase in inflammatory markers in BAL fluid and elevated malondialdehyde (MDA) levels with lower levels of intracellular reduced glutathione (GSH) in lungs of rats of co-exposed group. Significant increase in the levels of pro-inflammatory mediators (IL-6, Ikβα, Cox-II, p-NF-κB) in lung tissues also indicated pulmonary damage. To best of our knowledge this is the first study which highlights the toxicity of co-exposed ZnO NPs and toluene.